Healing process of dog teeth after post space preparation and exposition of the filling material to the oral environment - Barbosa, Henrian Gonzaga [UNESP]; Holland, Roberto [UNESP]; Souza, Valdir de [UNESP]; Dezan Junior, Eloi [UNESP]; Bernabé, Pedro Felício Estrada [UNESP]; Otoboni Filho, José Arlindo [UNESP]; Nery, Mauro Juvenal [UNESP] (Fundação Odontológica de Ribeirão Preto, 2003)
Foi propósito deste estudo analisar a influência da infiltração marginal coronária no comportamento dos tecidos periapicais de dentes de cães após obturação de canal e preparo para pino. Quarenta canais de dentes de cães foram instrumentados e obturados pela técnica da condensação lateral com cones de guta percha e os cimentos Roth e Sealer 26. Após preparo para pino, o remanescente da obturação foi protegido ou não com um plug do cimento temporário Lumicon. Após exposição ao meio oral por 90 dias, os animais foram sacrificados e as peças preparadas para análise histomorfológica. A técnica de Brown e Brenn mostrou 70% de casos com infiltração de microrganismos para o cimento Roth e 20% com o Sealer 26. Quando um plug de Lumicon foi empregado ocorreu 30% de casos de infiltração de microrganismos com o cimento Roth e 0,0% com o cimento Sealer 26. Reação inflamatória crônica foi mais freqüentemente observada com o cimento Roth do que com o Sealer 26. Foi concluído que o plug de Lumicon é eficiente no controle da infiltração coronária (p=0.05) e que o Sealer 26 foi mais biocompatível e selou melhor os canais radiculares do que o cimento Roth (p=0.01).

The purpose of this study was to observe the influence of coronal leakage on the behavior of periapical tissues after root canal filling and post space preparation. Forty root canals of dogs' teeth were instrumented and filled by the lateral condensation technique with gutta percha points and the cements Sealer 26 and Roth. After post space preparation, the remaining filling material was either protected or not protected with a plug of the temporary cement Lumicon. After root canal exposition to the oral environment for 90 days, the animals were killed and specimens were removed and prepared for histomorphological analysis. The Brown and Brenn technique showed 70% of cases with microorganism leakage for Roth cement, and 20% with Sealer 26. When a plug of Lumicon was employed, there was 30% leakage for Roth cement and 0% for Sealer 26. A chronic inflammatory reaction was more frequently observed with Roth cement than with Sealer 26. It was concluded that a plug of Lumicon was efficient in controlling microorganism coronal leakage (p=0.05), and that Sealer 26 was more biocompatible and sealed root canals better than Roth sealer (p=0.01).
Keywords: coronal leakage; post space preparation; Lumicon; Roth cement; Sealer 26